2021
DOI: 10.3390/ijms222111766
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Analysis of B-Box Transcription Factors in Strawberry Reveals the Role of FaBBx28c1 in the Regulation of Flowering Time

Abstract: Flowering connects vegetative and generative developmental phases and plays a significant role in strawberry production. The mechanisms that regulate strawberry flowering time are unclear. B-box transcription factors (BBXs) play important roles in the flowering time regulation of plants. Nevertheless, BBXs in octoploid cultivated strawberry (Fragaria ananassa) and their functions in flowering time regulation have not been identified. Here, we identified 51 FaBBXs from cultivated strawberry and 16 FvBBXs from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…In our previous study, a total of 51 members of the BBX family were identified in octoploid strawberry [ 52 ], but most of their functions are unknown. In this work, specific primers were designed to amplify the FaBBX22 gene, according to the transcriptome data described in the previous study [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, a total of 51 members of the BBX family were identified in octoploid strawberry [ 52 ], but most of their functions are unknown. In this work, specific primers were designed to amplify the FaBBX22 gene, according to the transcriptome data described in the previous study [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, a total of 51 members of the BBX family were identified in octoploid strawberry, and a BBX gene ( FaBBX22 ) was found to be differentially expressed during light quality treatment on strawberry [ 52 ]. In the present study, the FaBBX22 gene was isolated from the cultivated strawberry variety ‘Benihoppe’.…”
Section: Introductionmentioning
confidence: 99%
“…AtBBX28 , a repressor of light signaling, delayed the flowering time in Arabidopsis under long day conditions ( Lin et al, 2018 ; Liu et al, 2020 ). Furthermore, heterologous expression of strawberry FaBBX28C1 have been found to negatively regulate the flowering time in Arabidopsis ( Ye et al, 2021 ). In this study, there existed drought response and hormone response cis -elements in IbBBX28 -Pro, including MBS, P-box, ABRE, CGTCA-motif.…”
Section: Discussionmentioning
confidence: 99%
“…The amplified CDS of FaZAT10 and green fluorescent protein (GFP) was inserted into the plasmid vector (PYTSL-16) by homologous recombination, which was modified with pMDC83-35S and Psite-2NB [ 53 ]. The fusion expression of FaZAT10 and GFP (FaZAT10:GFP) was driven by the 35S promoter, and the nuclear localization maker for HY5-mCherry had the same 35S promoter drive [ 54 ].…”
Section: Methodsmentioning
confidence: 99%